DIFFERENCES IN THE EFFECTIVENESS OF USING A SITZ BATH AND INFRARED LIGHT THERAPY IN HEALING PERINEAL WOUNDS IN POSTPARTUM MOTHERS AT PMB MIDWIFE NOVIA DEWI IN 2024 - Dewi, Novia; Assyaidah, Sonda Nur (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background : Perineal wounds are the most common maternal morbidity associated with normal birth. Long-term morbidity associated with repair of unrecognized external sphincter injuries or trauma can cause major physical, psychological and social problems. Perineal damage can have a major negative impact on women's health. Non-pharmacological therapies that can be given to reduce pain and speed up healing include sitz baths and infrared. Objective: To determine the difference in the effectiveness of using sitz baths and infrared light therapy in healing perineal wounds in postpartum women at PMB Midwife Novi in ​​2024. Method: This research is a quantitative research with a quasi-experimental design, the design used is a pretest and post test non-equivalent control group approach. The population in this study were all postpartum mothers with perineal wounds at PMB Bidan Novi in ​​June 2024, totaling 64 postpartum mothers. The research sampling technique used total sampling. The sample in this study was 64 postpartum mothers who were at PMB Midwife Novi 2024 in June, 32 postpartum mothers with sitz bath intervention and 32 postpartum mothers with infra red intervention. Results: The research results showed that with a p value of 0.044 < 0.05, the results of the Mann Whitney test showed that postpartum mothers who were given sitz baths and infrared lamps healed their perineal wounds differently. Sitz bath (average value 1.09) accelerates perineal wound healing compared to infrared lamps (average value 1.84). The results show that there is a significant difference between the use of sitz baths and infrared lamps in healing perineal wounds, the use of Sitz Baths is more effective for healing perineal wounds in postpartum mothers compared to the use of infrared. Conclusion: There is a significant difference between the use of sitz baths and infrared lamps in healing perineal wounds, the use of Sitz Baths is more effective for healing perineal wounds in postpartum women compared to the use of infrared (p value 0.044 < 0.05).